The Ring - Verbinski, Gore, 1964-; Tamblyn, Amber; Brian Cox; David Dorfman; Jane Alexander; Lindsay Frost; Martin Henderson; Naomi Watts (USA, Japan DreamWorks SKG, 2002)
When her niece spontaneously dies of fright one week to the day she watched a disturbing video, a cynical journalist (Naomi Watts) travels to the Pacific Northwest in search of the tape's origins and its links to a string of suicides at a horse ranch.
A young journalist must investigate a mysterious videotape which seems to cause the death of anyone in a week of viewing it.
Kôji Suzuki
Languages : English, Polish Subtitles : English, Turkish, Greek
Keywords: Horror; Mystery; Thriller; Drama